Organocatalyzed Synthesis and Antifungal Activity of Fully Substituted 1, 4‐Dihydropyridines. Issue 24 (25th June 2018) - Khan, M. Musawwer; Saigal,; Khan, Sarfaraz; Shareef, Sumbulunnisan; Danish, Mohammad
Abstract: An efficient one‐pot four‐component domino reaction for the convenient access of fully diversified 1, 4‐dihydropyridines (1, 4‐DHPs) from simple starting materials using basic organocatalyst is demonstrated. These derivatives were synthesized in good to excellent yields via the reaction between dialkyl acetylenedicarboxylates, arylamines, malononitrile, and aromatic aldehydes catalyzed by 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU) in ethanol at room temperature. The molecular structure of 1, 4‐DHP derivative5 h was confirmed by the single crystal X‐ray analysis. Mild reaction conditions, short reaction time, applicable to a broad range of substrates and simple experimental procedure are some of the salient features of the present protocol. In addition, the synthesized compounds were screened against Aspergillus niger (MTCC‐281), Aspergillus fumigates (MTCC‐343) and Claviceps purpure for in vitro antifungal activity and noted that most of the compounds were exhibit good to excellent antifungal activities compared to the standard reference. Abstract : An efficient and practical method was developed to synthesize 1, 4‐dihydropyridines (DHPs) by the reaction between dialkyl acetylenedicarboxylates, arylamines, malononitrile, and aromatic aldehydes using DBU as a base in ethanol at room temperature. Synthesized compounds were screened for in vitro antifungal activities using Nystatin as the standard reference. Some of them synthesised molecules were exhibited excellent antifungal activities.